2009
DOI: 10.1007/s11355-009-0064-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of total submergence in saltwater on growth and leaf ion content of preflooded and unflooded Taxodium distichum saplings

Abstract: Preconditioning by hypoxic condition would contribute higher tolerance to anoxic condition in physiological and metabolic aspects of various plant species. In expectation of improvement of salinity tolerance, effects of preconditioning with soil flooding on growth responses and photosynthetic activity in relation to Na ? content in leaves and roots were studied using 2-year-old Taxodium distichum saplings. A submergence experiment was performed at three salt concentrations (0, 4000, and 8000 ppm NaCl), and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…T. distichum saplings submerged in saltwater showed no morphological changes during the flooding treatment. However, leaf injury and shoot dieback were observed in drained saplings submerged in saltwater (Iwanaga et al 2009). Lei and Middleton (2018) investigating seed banks in the Mississippi River Alluvial Valley and the northern Gulf of Mexico, found that repeated droughts reduced the regenerative capacity of T. distichum seeds.…”
Section: Popular Research Areasmentioning
confidence: 99%
“…T. distichum saplings submerged in saltwater showed no morphological changes during the flooding treatment. However, leaf injury and shoot dieback were observed in drained saplings submerged in saltwater (Iwanaga et al 2009). Lei and Middleton (2018) investigating seed banks in the Mississippi River Alluvial Valley and the northern Gulf of Mexico, found that repeated droughts reduced the regenerative capacity of T. distichum seeds.…”
Section: Popular Research Areasmentioning
confidence: 99%